Optimalisasi Proses Manufaktur dalam Pembuatan Pipa Union dengan Menggunakan Metode Hungarian dan PERT/CPM - Rianita Puspa Sari; Okky Jayadi; Langgam Tandya Nugraha (Universitas Bunda Mulia, 2018)
CV. Faresti Prima which is a company engaged in machining, automatic part, dies, and jigs. Union Pipe Unit is part of the research because it has problems in the assignment that is still manual. Data collection is done on unit union pipe with average work per day. The problem is found in the union pipe unit with the manual assignment. Observations made on 4 people for cutting pipes, chamfering, stamping, and packing. Results of observations then performed data processing using Hungarian method, so that the optimum unit is generated per hour as much as 8.125. Furthermore, data processing was performed using PERT method with the result stated that the optimum working order was A-B-C-D-E with total processing time for 5,000 units for 16.5 hours. The last data processing using CPM method can be seen that the acceleration time as much as 8 hours from the initial time is 16.5 hours with the total crash cost of 4,000,000 IDR from the allocated fund of 4,225,000 IDR. From some data processing, it can be seen that there is an optimization in the assignment and network work. Therefore, in accordance with the existing theories and objectives of this research, namely to optimize the existing human resources for the work done equally and minimize the losses due to unemployed use of these methods can be used as a reference in the making of the schedule, so as to facilitate the course of the project to know the delay in every process.